STRATEGI PENINGKATAN GARAP CATUR DI SANGGAR PEDALANGAN SERENGAN SURAKARTA - Bagong Pujiono (Abdi Seni, 2016)
The learning condition in puppetry studio Serengan is not systematically arranged yet so it needs an improvement. The study of garap pakeliran with the teaching material given is supposed to actualize a better result by maximizing the being human resource. One aspect of pakeliran that must be fulfilled in puppet theater is catur. The method used in the study of pakeliran practice in puppetry studio Serengan is appreciation, speech, and demonstration. Based on the method used, it can be concluded that students are successfully able to  catch catur of the characters in the short pakeliran lakon Gathotkaca Sungging presented by Ki Nartasabda which has been edited by Purbo Asmoro. Garap Catur is including janturan, pocapan, and ginem of the characters: Duryudana, Baladewa, Durna, Karna, Sengkuni, Nilayaksa, Kartamarma, Jayadrata, Gathotkaca, Samba, Setyaki, Antareja, Dewapawaka, Abimanyu, Semar, Gareng, Petruk, Bagong, Pragalba, Anoman, Arjuna, Banowati, Lesmanawati, and Bhatara Guru.Key words : studio, puppetry, ginem, janturan, and pocapan.